The Caribbean Diaspora and the Formation of Identity in Second Generation Immigrants - Leonika Valcius (Caribbean Studies Students' Union, 2012)
Leonicka Valcius is an undergraduate student at the University of Toronto, studying Caribbean Studies and European Studies. Her areas of focus include migration and the social ramifications of economic development. Leonicka was born in Montreal and raised in South Florida. Her family immigrated to Canada from Haiti in the 1970's, and they have since spread all over North America and the Caribbean. Leonicka has familial ties to Montreal, Toronto, New Jersey, New York, Boston, Florida, the Bahamas, Cuba, the Dominican Republic, and, of course, Haiti chérie .